Heat Induces Oxidative Stress: Reproductive Organ Weights and Serum Metabolite Profile, Testes Structure, and Function Impairment in Male Cavy (Cavia porcellus) - Ngoula, Ferdinand; Lontio, Fulbert Aime; Tchoffo, Herve; Manfo Tsague, Faustin Pascal; Djeunang, Roméo-Marcial; Vemo, Bertin Narcisse; Moffo, Frederic; Djuissi Motchewo, Nadege (Frontiers in Veterinary Science, 2020)
The present study was designed to evaluate the effects of heat stress that induces on oxidative stress on reproduction organ weight and serum biochemical, testes structure and function in male guinea pig (Cavia porcellus). Forty-eight male guinea pigs with an average weight of 330.56 ± 23.62 g, aged 3-4 months were distributed into 4 groups of twelve animals each. One group (control) was maintained to ambient temperature (20-25 °C °C), while other groups (Groups 2- 4) were exposed daily for 6 hours, to 32±1 °C, 39±1°C and 46±1 °C, respectively. A All animals were sacrificed after 60 days exposure and their reproductive characteristics values determined. Results revealed a significantly decrease (p<0.05) of the weight of testes, epididymis, vas deferens and accessory sex glands in cavies exposed to the highest temperature investigated (46 °C) compared to the control animals. There was significant (p<0.05) reduction of serum testosterone and LH levels in all heat stress-exposed groups when compared to the control group. Heat stress significantly (p<0.05) decreased sperm mobility, sperm count and testicular antioxidant enzymes, while increasing testicular malondialdehyde content. However, serum level of HSP 40 increased in the animals exposed to 39 °C and decreased when the cavies were exposed to 46 ±1 °C.In conclusion, exposure to heat induced oxidative stress which results in impairment of reproductive organ weights and serum biochemical parameters, testes structure and function in male cavy.